Iranian Junior High School Teachers' Perceptions and Attitudes towards their Newly-Published English Textbooks: A Study on Communicative Approach - Rasti, Jafar; Behjat, Fatemeh; Kargar, Ali Asghar (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
Iranian students start learning English as a foreign language from Grade Seven in the first grade of junior high school to Grade Twelve in their formal educational system. However, their weak English production has encountered educational system with this serious question why students are not able to speak English despite a six-year instructional period at school. Since one of the effective factors in teaching a language is the textbook, this study focuses on the content of textbooks and teachers' attitudes toward the newly-published English textbooks. The study evaluates the quality of the Seventh Grade English language textbook, Prospect 1, for Iranian junior high school students, which was introduced first by the Ministry of Education in 2013. This research project evaluates the new textbook that is considered to be a fundamental shift in the English language schoolbooks in Iran. A questionnaire was used in this study to elicit the perspectives of 44 English language teachers. The questionnaire consisted of 40 items grouped under 7 main categories: Practical Considerations, Layout and Design, Activities, Skills, language type, subject and content, and conclusion. The data was subjected to analysis through descriptive statistics. The data were analyzed quantitatively. For the analysis of the responses to the questionnaires, Statistical Package for Social Sciences (SPSS 19.0) was used, and necessary calculations were carried out. The data in the questionnaire were analyzed using mean scores and standard deviations. The findings were generally in favor of the textbook except for the skills. The findings also revealed despite usual teachers' resistance to new changes, they have positive views toward the newly- published book. Moreover, although teachers' satisfaction in Conclusion, Layout and design, and Language Type is rather high, it seems they need more attention in comparison with Practical Consideration, Activities and Subject and Content.